HOSPITAL-ACQUIRED URINARY TRACT INFECTIONS IN CANCER PATIENTS - N. V. Dmitrieva; I. N. Petukhova; Z. V. Grigorievskaya; N. S. Bagirova; I. V. Tereshchenko; V. V. Aginova; I. A. Klyuchnikova; S. A. Dyakova; A. I. Dmitrieva; T. A. Kalinchuk (Сибирский онкологический журнал)
Introduction. Urinary tract infections are among the most frequently seen bacterial infections. Worldwide, about 150 million people are diagnosed with urinary tract infections each year, costing the global economy in excess of 3.5 billion US dollars. Urinary tract infections occur more frequently and exhibit more severe symptoms in cancer patients than in patients with other diseases. Material and methods. The paper analyzes the etiology of urinary tract infections in cancer patients during their stay in the hospital. Results. The presented data concern antibiotic-resistant ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species). Comparative data on the sensitivity to different antibiotics were shown. Recommendations for treatment aimed at reducing the selective pressure of certain groups of antibiotics, in particular carbapenems, were given.